The 'Rainbow Alliance' or the Focus Group? Sexuality and Race in the Labour Party's Electoral Strategy, 1985–7. (5th July 2019) - Murphy, C
Abstract: In the 1980s, Labour struggled to respond to a hostile political context during a protracted period of opposition. Diverse figures claimed that the Left was suffering from a structural decline in a supposed 'traditional working class' voting base: contentions which only became more influential after the 1983 electoral catastrophe. Competing solutions were proffered—including building a 'rainbow alliance' informed by equalities politics, or appealing to a southern 'new working class'. The latter interpretation gained greater influence on Neil Kinnock's leadership. To fully understand why one triumphed over the other in the evolving strategy of the Labour Party, we should in part trace discourses, including contemporary 'loony Left' scandals. However, we must also recognize the importance of 'epistemological practice', which was crucial in shaping how political actors acquired knowledge and forged interpretations of the electorate. Focusing on the evolution of the epistemological practice of Kinnock's leadership team—in particular, their increasing reliance on qualitative opinion research techniques like focus groups to supplement quantitative attitudinal polling—helps explain why they became convinced that recent controversies involving race and sexuality were having acutely negative consequences for Labour nationally. This furnishes us with a deeper understanding of the relationship between grassroots and national Left-wing politics in the 1980s. It also illuminates Labour's cautious approach to equalities politics into the 1990s.